HUBUNGAN MOBILISASI DINI DENGAN KESEMBUHAN LUKA PERINEUM DERAJAT DUA PADA IBU POSTPARTUM - Novita Br Ginting Munthe; Iskandar Markus Sembiring; Putri Indra Gandi; Kuat Sitepu; Vitrilina Hutabarat; Stefani Anatasya Sitepu (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2020)
Labor was a natural and physiological thing experienced by a woman. However, those were times when labor could caused traumatic problems for a woman who could increased maternal morbidity and mortality. The problem of morbidity that often arises due to vaginal delivery was the occurrence of lacerations in the perineum, can occur spontaneously during labor, especially in primiparous mothers or mothers who have given birth for the first time. Mobilization not only speeds up the healing of perineal wounds but also restores the body's condition if done properly and correctly. This study aimed to determine the relationship of early mobilization to the healing of second degree perineal wounds in post partum mothers at the Nining Pelawati Clinic Kecamatan Lubuk Pakam Kabupaten Deli Serdang in 2019. This type of research was quantitative with cross sectional design. The population in this study were all postpartum mothers at the Nining Pelawati Clinic. The sampling technique used accidental Sampling with a sample size of 20 people. Collecting data with a questionnaire. Data analysis was done by univariate, bivariate with Chi-square test at 95% confidence level, α = 5%. The results of the analysis showed that there was a relationship between early mobilization to the healing of second degree perineal wounds in post partum mothers at the Nining Pelawati Clinic Kecamatan Lubuk Pakam Kabupaten Deli Serdang in 2019 with value of p = 0.020. It is recommended to post partum mothers to carry out early mobilization after the delivery process to improve wound healing.